Breath‐holding physiology, radiological severity and adverse outcomes in COVID‐19 patients: A prospective validation study. Issue 12 (7th August 2022) - Messineo, Ludovico; Fanfulla, Francesco; Pedroni, Leonardo; Pini, Floriana; Borghesi, Andrea; Golemi, Salvatore; Vailati, Guido; Kerlin, Kayla; Malhotra, Atul; Corda, Luciano; Sands, Scott
Abstract: Background and objective: COVID‐19 remains a major cause of respiratory failure, and means to identify future deterioration is needed. We recently developed a prediction score based on breath‐holding manoeuvres (desaturation and maximal duration) to predict incident adverse COVID‐19 outcomes. Here we prospectively validated our breath‐holding prediction score in COVID‐19 patients, and assessed associations with radiological scores of pulmonary involvement. Methods: Hospitalized COVID‐19 patients ( N = 110, three recruitment centres) performed breath‐holds at admission to provide a prediction score (Messineo et al.) based on mean desaturation (20‐s breath‐holds) and maximal breath‐hold duration, plus baseline saturation, body mass index and cardiovascular disease. Odds ratios for incident adverse outcomes (composite of bi‐level ventilatory support, ICU admission and death) were described for patients with versus without elevated scores (>0). Regression examined associations with chest x‐ray ( Brixia score) and computed tomography (CT; 3D‐software quantification). Additional comparisons were made with the previously‐validated '4C‐score'. Results: Elevated prediction score was associated with adverse COVID‐19 outcomes ( N = 12/110), OR[95%CI] = 4.54[1.17–17.83], p = 0.030 (positive predictive value = 9/48, negative predictive value = 59/62). Results were diminished with removal of mean desaturation from the prediction score (OR = 3.30[0.93–11.72]). The prediction score rose linearly with Brixia score ( β [95%CI] = 0.13[0.02–0.23], p = 0.026, N = 103) and CT‐based quantification ( β = 1.02[0.39–1.65], p = 0.002, N = 45). Mean desaturation was also associated with both radiological assessment. Elevated 4C‐scores (≥high‐risk category) had a weaker association with adverse outcomes (OR = 2.44[0.62–9.56]). Conclusion: An elevated breath‐holding prediction score is associated with almost five‐fold increased adverse COVID‐19 outcome risk, and with pulmonary deficits observed in chest imaging. Breath‐holding may identify COVID‐19 patients at risk of future respiratory failure. Abstract : An elevated breath‐holding‐based prediction score was associated with increased COVID‐19 incident adverse outcome risk in a validation cohort of 110 hospitalized COVID‐19 patients. The prediction score was also positively associated with increasing radiological severity, per chest x‐ray and computed tomography (CT) assessment. Our prediction score performed better than the previously‐validated, biomarker‐based 4C‐score.